Sex Offenders Seeking Treatment for Sexual Dysfunction—Ethics, Medicine, and the Law. (10th June 2015) - Phillips, Elizabeth A.; Rajender, Archana; Douglas, Thomas; Brandon, Ashley F.; Munarriz, Ricardo
Abstract Introduction The treatment of sexual dysfunction in patients with prior sexual offenses poses ethical and legal dilemmas. Sex offenders are not obligated by law to disclose this history to medical professionals. Over 20% of sex offenders experience sexual dysfunction; however, the number of sex offenders seeking evaluation for sexual dysfunction is unknown. Aims The aims of this study were to determine the incidence and characteristics of sex offenders seeking treatment in our clinic; and to review data regarding sex offender recidivism and ethics pertaining to the issue as it relates to treating physicians. Methods Sex offenders were identified via three methods: new patient screening in a dedicated sexual medicine clinic, chart review of those on intracavernosal injection (ICI) therapy for erectile dysfunction (ED), and review of patient's status‐post placement of penile prosthesis. Charts were cross‐referenced with the U.S. Department of Justice National Sex Offender Public Website. Patient characteristics and details of offenses were collected. Main Outcome Measures The main outcome measures used were a self‐reported sexual offense and national registry data. Results Eighteen male sex offenders were identified: 13 via new patient screening; 3 by review of ICI patients; 1 by review of penile prosthesis data; and 1 prior to penile prosthesis placement. All were primarily referred for ED. Of those with known offenses, 64% were level 3 offenders (most likely to re‐offend). The same number had committed crimes against children. All those with complete data had multiple counts of misconduct (average 3.6). Ninety‐four percent (17/18) had publicly funded health care. Twelve (67%) were previously treated for sexual dysfunction. Conclusions Registered sex offenders are seeking and receiving treatment for sexual dysfunction. It is unknown whether treatment of sexual dysfunction increases the risk of recidivism of sexual offenses. Physicians currently face a difficult choice in deciding whether to treat sexual dysfunction in sex offenders. Phillips EA, Rajender A, Douglas T, Brandon AF, and Munarriz R. Sex offenders seeking treatment for sexual dysfunction—Ethics, medicine, and the law. J Sex Med 2015;12:1591–1600.